1969
DOI: 10.12669/pjms.301.3197
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nitrous Oxide on Vascular Endothelial Growth Factor (Vegf) and Its Soluble Receptor 1 (Vegfr1) in Patient Undergoing Urological Surgery

Abstract: Objective: Anesthesia and surgical intervention, leads to the development of systemic inflammatory response. The severity of the inflammatory response depends on the pharmacological effects of anesthetic agents and duration of anesthesia. Objective of the study was to investigate the effect of nitrous oxide on VEGF and VEGFR1 levels in patients undergoing surgery. Methods: Forty-four patients undergoing elective urological surgery were included in the study. Anesthesia maintenance was provided with 1-2 MAC sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The main reason lies in the endogenous therapeutic angiogenesis is a complex physiological process [10]. Moreover, VEGF gene expression in vivo began at 4H after the appearance of the severe ischemia, peaked at 3-5 days, but gradually decreased on the 7th day [11,12]. Therefore, the endogenous restricted expression of VEGF can not satisfy with the concentration required for neovascularization in ischemic limb.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason lies in the endogenous therapeutic angiogenesis is a complex physiological process [10]. Moreover, VEGF gene expression in vivo began at 4H after the appearance of the severe ischemia, peaked at 3-5 days, but gradually decreased on the 7th day [11,12]. Therefore, the endogenous restricted expression of VEGF can not satisfy with the concentration required for neovascularization in ischemic limb.…”
Section: Discussionmentioning
confidence: 99%
“…As for vascular growth factors, one potential target is Vascular Endothelial Growth Factor (VEGF). Clinical studies have shown that VEGF expression levels decrease after exposure to nitrous oxide during urological surgery (Hakimoglu et al, 2014). Therefore, future studies investigating changes in vascular plasticity during early developmental exposure to anesthesia are needed.…”
Section: Blood Brain Barrier and Cerebrovasculaturementioning
confidence: 99%